The Study of Instagram Account of PCU Visual Communication Design Study Program and Its Competitor - Ryan P. Sutanto (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
The goal of this research is to get a general content overview from the Instagram account of Petra Christian University (PCU) Visual Communication Design (VCD) Study Program, and its competitor. The content of the Instagram accounts is analyzed with content analysis then compared. Instagram is seen as one of the media that can influence and reach greater target audiences. Nowadays, Instagram also closely relates to teenagers. The covid-19 pandemic has been hitting hard for every sector, including the educational sector. During the height of the pandemic, traditional marketing tools such as billboards and print ads became obsolete because people stayed at home and used their digital devices more than usual. The result of this research is meant to be a benchmark and strategy guide for the PCU VCD Study Program to manage their Instagram account.